1059. Staphylococcus aureus Bacteremia Treatment: Results From Pilot Surveillance in Four US States. (26th November 2018) - Kabbani, Sarah; Jackson, Kelly; Epstein, Lauren; Gellert, Anita; Bernu, Carmen; Overton, Rahsaan; Nadle, Joelle; Dumyati, Ghinwa; Lynfield, Ruth; Ray, Susan M; Epson, Erin; See, Isaac
Abstract: Background: Staphylococcus aureus treatment guidelines are being revised to include proposed quality measures for evaluation of patients with S. aureus bacteremia (SAB) (e.g., infectious disease [ID] consultation, echocardiogram, and documenting clearance of bacteremia). We describe current management practices of SAB to identify opportunities for quality improvement. Methods: We conducted a pilot assessment of SAB cases reported to CDC's Emerging Infections Program active, laboratory- and population-based surveillance from 24 hospitals in four states during 1–2 months in 2017 or 2018. An SAB case was the isolation of S. aureus from a blood culture among adults (≥18 years) in the catchment area. We collected clinical and demographic information and performed a descriptive analysis of management of SAB cases. Results: Among 109 SAB cases identified, 50 (46%) were methicillin-resistant S. aureus (MRSA). While hospitalized, 87 (80%) patients were evaluated by ID consultation, 90 (83%) underwent an echocardiogram (26 were transesophageal), and 92 (84%) had documented clearance of bacteremia. During the hospitalization, 15 (14%) died and 12 (11%) left against medical advice (AMA). Of those who survived and did not leave AMA, median duration of hospitalization after initial culture was 10.5 days (interquartile range 7–18). In total, 10 survivors (9% of cases) completed at least 2 weeks of antibiotics while hospitalized, and 65 (60% of cases) were discharged on antibiotic therapy. Among the 25 MRSA patients discharged on antibiotics, common treatments were vancomycin (64%), daptomycin (8%), ceftaroline (8%), and linezolid (4%). Among the 40 methicillin-susceptible SAB patients discharged on antibiotics, cefazolin (56%), ceftriaxone (13%), cefepime (5%), linezolid (5%), nafcillin (3%), and vancomycin (3%) were most common. The remainder of outpatient treatments included oral β-lactams, clindamycin, doxycycline, levofloxacin, and erythromycin. Conclusion: Overall, the majority of patients with SAB underwent evaluation according to the proposed quality measures and received therapy with targeted anti-staphylococcal agents, although opportunities to optimize treatment remain. Hospitalized patients who leave AMA represent a particular challenge for effective SAB therapy. Disclosures: All authors: No reported disclosures.